Incidencia de riesgos mecánicos en la seguridad y salud ocupacional de los trabajadores de la planta de balanceados de la ESPAM MFL - Bravo Cevallos, Erwin Paúl (2016)
This research was presented as main objective to assess the impact of mechanical risk factors in occupational safety and health of workers of the plant balanced meal and the ESPAM "MFL". We proceeded to develop the theoretical framework as a reference to substantiate the object of study, the methodology used corresponded to a descriptive study, which was necessary to make a situational analysis that led to the problem area, problems and shortcomings that were detected following the procedure for the General SWOT analysis of the plant, determining the main problem with the stipulated solution and strategy. The techniques were field investigation, scientific observation, surveys and interviews. Furthermore by applying the Matrix Triple Criterion existing risks they were established on the ground for a total of 12 factors (6 moderate risks and 6 major risks) performing the analysis, preventive measures and / or personal protective equipment for each. As a last point of the investigation following the basis of the information collected proceeded to propose a plan occupational safety and health based on mechanical risks in order to contribute more performance logistics plant worker health and providing an environment suitable employment.